The value of the early unwind option in futures contracts with an endogenous basis - Wolfgang Bühler; Alexander Kempf (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1994)
In this paper the implicit early unwind option of a risk neutral arbitrageur is valued. The problem is analyzed in a market microstructure framework where four different groups of market participants interact. Within this model the equilibrium price relationship between stock and futures markets is determined. Since the underlying of the option is influenced by arbitrage trading the underlying of the option depends contrary to standard option pricing theory on the unwind option itself. The non-Markovian stochastic process of the basis is characterized and the results of an extensive comparative static analysis of the option value are presented.
Keywords: 330; Termingeschäft; Arbitragegeschäft; Capital Asset Pricing Model; Theorie